GAMBARAN FAKTOR-FAKTOR TERJADINYA ASFIKSIA PADA BAYI BARU LAHIR DI PUSKESMAS BANJARNEGARA 2 KABUPATEN BANJARNEGARA - Lia Aria Ratmawati; Dewie Sulistyorini (Jurnal Ilmiah Medsains, 2020)
Child health efforts are expected to reduce child mortality. One of the indicators is the Infant Mortality Rate. The purpose of this study was to determine the description of the factors of asphyxia in newborns at the Banjarnegara Puskesmas 2 Banjarnegara District. This type of quantitative research is analytic survey design, cross sectional approach method. The population is all mothers who give birth to newborns with asphyxia in January - May 2020 at the Banjarnegara Health Center 2 as many as 22 newborns with asphyxia. The sampling technique uses total sampling. Univariate analysis looked at the frequency distribution and the percentage of each variable studied, namely maternal age, maternal parity, gestational age, difficult delivery and amniotic fluid conditions. The results of the study are mothers who give birth to newborns with asphyxia, the majority of those at low risk are 77.27%. Parity of mothers giving birth all included in the category of primipara and grandemultipara by 100%. The gestational age of mothers in all categories of term pregnancy is 100%. The majority of asphyxia occurs in mothers with difficult births in the amount of 90.91%. The condition of amniotic fluid the majority of amniotic fluid mixed with meconium of 68.18%.